The naming of child homicide offenders in England and Wales: the need for a change in law and practice - Fitz-Gibbon, Kate (The British journal of criminology, 2017)
Judicial decisions about whether or not to publicly name child homicide offenders have long animated debate in the United Kingdom and internationally. This article draws on case law and in-depth interviews conducted with members of the English criminal justice system to critically analyse the viability of current domestic legislation in the context of the UK’s international human rights obligations. The article identifies ambiguities surrounding the definition of ‘public interest’ in law; the merits of equating the naming of child offenders with open justice, accountability and transparency; and the increasing sabotage of the principle of rehabilitation. By identifying the complexities of this contentious area of judicial discretion, this article highlights the need for a rights-based approach to decisions about publicly naming children in conflict with the law.